Analysis, Modeling and Modification of a Wideband Hom Antenna with a Skate Transition - Fedorov, S. A.; Kuptsov, M. I.; Kuptsov, I. M. (2019 International Conference on Engineering and Telecommunication (EnT), 2019)
The article presents and discusses the results of modeling a wide-band horn antenna with a ridge transition. Based on the model and experimental measurements, an analysis of the set of antenna characteristics is carried out and its modification is proposed. In the modification of the antenna, a radar absorbing material with a thickness of 10 mm is used, which significantly reduces the uneven distribution of the field in the near zone of the antenna. The distribution of the field amplitude for the modernized antenna (with the application of radar absorbing material) has an enlarged region of the "quasiplane" wave. The phase distribution of the field becomes more compact.